Breaking Bad: Existential Threat Decreases Pro-Environmental Behavior. Issue 3 (4th May 2017) - Buttlar, Benjamin; Latz, Marc; Walther, Eva
ABSTRACT: Why is it that people do not change their behavior in the face of global threats? We hypothesized that when people who have been encouraged to engage in pro-environmental behavior are threatened, they fall back into their (bad) habits instead of exhibiting behavioral change; existential threats may thereby counteract pro-environmental norms. We tested this hypothesis in two field studies in which participants were encouraged to reduce paper use. Although the requests initially resulted in decreased paper use, this pro-environmental behavior ceased when an existential threat was induced. We discuss theoretical and practical implications for social psychology theorizing and behavioral change.